Comments on Friis Transmission over a Ground Plane (Global Journal of Computer Science and Technology, 2022)
The Friis Equation 1 had been used to calculate the power budget between antenna gains and space losses in any radio link with no obstructions in the path between the antenna elements 10 It can be used to obtain perfect answers when applied to links in free space and over perfect ground without any modifications or additions